Optimization and validation of the preconcentration technique with SBSE coupled HPLC-UV/DAD for the identification of atrazine and two of its metabolites: 2-Hydroxyatrazine (2-HA) and Desethylatrazine (DEA) in aqueous samples - García Villanueva, Luis Antonio; Fernández Villagómez, Georgina; Andraca Ayala, Gema Luz; Yáñez Campuzano, José Mauricio; Zamora Martínez, Olivia; Martínez Castro, Juan Ramón (My University, 2024)
Agriculture is the science of cultivating the land to obtain raw materials. The main reasons that have led to agricultural production have been to solve the problem of world hunger through the extensive use of agricultural practices (Carmona 2004). Mexico uses 76% of its renewable water for agriculture, which mainly produces sugarcane, corn and sorghum. During its cultivation, atrazine has been found to be used as a pesticide for weed control. Studies worldwide consider atrazine as an endocrine disruptor, even low doses of pesticides can alter the biochemical profile, resulting in oxidative stress within the population’s brains causing hormonal imbalance and is classified as a carcinogenic substance, it also represents various risks to the aquatic environment and its propagation in it, so it has been banned in some countries (CICOPLAFEST 2005, IARC 2014, Sharma et al 2023). There are studies where residual pesticides are detected in soil, water, food, biological fluids and tissue samples. In food, different pesticides have been found in cereal grains, cactus, shrimp, vegetable oils, tomato, grapes, among others (Ahmed et al. 2009, Aldana et al. 2008, Alsayeda et al. 2008). Hence the interest in studying the persistence of pesticides in the environment. Atrazine is one of the most widely used pesticides in the world and Mexico is the second country where it is used in the greatest quantity, and where there is no law prohibiting or regulating its use. It should be noted that some Mexican standards provide maximum permissible limits in a preventive manner, mainly those referring to drinking water, wastewater discharges and food (Bello 2016, FAO 2016, González-Márquez & Hansen 2009). In the practice of chemical analysis there are countless reasons to perform tests, measurements and examinations in laboratories worldwide, for example, to control the quality of drinking and irrigation water, food, medical analysis, high value-added products among many others, which require high reliability since important decisions depend on the results that these measurements produce (Eurolab 2016). That is why it is considered necessary that the methods of analysis, as well as the analytical results are subjected to some acceptance criterion that allows them to document their quality and verify that the experimental procedures meet the quality criteria requested by the customer and are suitable for the specific use for which they were developed. This procedure is known as method validation and is applied by countless laboratories around the world (CDER 1994).
The purpose of this work is to address an environmental problem in Mexico, which uses significant amounts of water for agricultural activities, where atrazine is frequently used as a pesticide for weed control. Currently there is no law prohibiting its use, despite the fact that it is considered an endocrine disruptor in some mammals and harmful to health. Due to the difficulty in the direct quantification of several herbicides, which present a low concentration in water, the present work aims to develop the optimization and validation of the preconcentration with magnetic stir bars (SBSE) in aqueous samples for the quantification of atrazine and two of its metabolites: 2-hydroxyatrazine (2-HA) and desethylatrazine (DEA), coupled to High Performance Liquid Chromatography (HPLC-UV/DAD). For the optimization of the preconcentration technique, the nature and quantity of the solvents used in each step, contact time for retention and quantitative extraction of the analyte, as well as the effect of the concentration of the analyte on its retention on the bar were considered. Finally, it was determined that the presence of the metabolites 2-HA and DEA does not affect the sorption of atrazine on the sorption bar used. The analytical methodology can be considered as an efficient method of atrazine preconcentration for subsequent quantification via HPLC-UV/DAD in the range of 0.03 to 0.25 mg/L and in the absence of matrix interferences; its limits of detection and quantification are respectively 0.0014 mg/L and 0.0016 mg/L.
Keywords: Atrazine; High performance liquid chromatography; Diode array detector; SBSE; Triazines; Organochlorine pesticide